'We All Go a Little Mad Sometimes. Haven't You?' Musical Empathy in Hitchcock's Psycho. (22nd February 2018) - CLIFTON, KEVIN
ABSTRACT: This essay explores a web of cognised and embodied empathies that emerge while watching Hitchcock's Psycho, focusing on the role of musical empathy as it relates to Marion Crane's story. Drawing on work on empathetic music in film music studies, I explore how the actors, the characters, the musical score and the filmic audience are drawn together by a 'sigh' figure, a symbolic gesture that unifies the soundtrack.